Metallocene catalysts on complex magnesium support modified by organoaluminium compounds - Nowakowska, M.; Ochędzan-Siodłak, W.; Kordowska, M. (Polimery, 2022)
A support modified by organoaluminum chloride or MAO enabled us to obtain specjally active zirconocene catalyst systems for ethylene polymerization. The zirconocene system on the bimetallic support was found to be the more active than that on the monometallic support.